Triggering Organizational Effectiveness: Exploring Its Profound‎Impact of Organizational Culture in The Retailers of Odisha - Chandrasekhar, Karnam; Das, Dr. Saumendra; Gupta , Dr. Neha (International Journal of Accounting and Economics Studies, 2025)
This study investigates the catalysts of organizational effectiveness and their profound impact on ‎organizational culture in the retail sector of Odisha. With the retail industry booming in India, ‎driven by economic growth, demographic shifts, and evolving consumer preferences, this ‎research explores the crucial role of top management in fostering a culture of equality, delegation, ‎and customer-centricity. A survey of 102 customers in Bhubaneswar city reveals that top ‎management's attitude towards customers, delegation to subordinates, and policies facilitating ‎customer development significantly influence organizational effectiveness. The findings suggest ‎that top management plays a pivotal role in creating a conducive environment that empowers ‎employees to deliver exceptional customer satisfaction, ultimately triggering a culture of ‎excellence in retail organizations‎.